2014
DOI: 10.1007/s00405-014-3211-3
|View full text |Cite
|
Sign up to set email alerts
|

Are subjective assessments of snoring sounds reliable?

Abstract: The aim of this study is to investigate whether snoring sounds can be reliably, i.e. reproducibly and comparably, assessed by the listener. This is an absolute prerequisite if an objective method is to provide a valid representation of subjective assessments of snoring sounds. Fifty-three subjects, both men and women, from different age categories assessed snoring sequences in terms of their annoyance level. This was done using a paired comparison model with ten sequences, once at original volume and once at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…As snoring sounds are commonly described as a nuisance by the bed partner of the affected individual, information on snoring was collected from a bed partner or family member. Snoring intensity was evaluated using a 10 cm visual analogue scale (VAS) from 0 to 10: 0 represents no snoring, 1–3 represents minimally annoying, 4–6 represents moderately annoying, 7–9 represents annoying, and 10 represents extremely annoying [18]. We defined 0 as no snoring, 1–3 as mild snoring, 4–6 as moderate snoring, and 7–9 as severe snoring.…”
Section: Methodsmentioning
confidence: 99%
“…As snoring sounds are commonly described as a nuisance by the bed partner of the affected individual, information on snoring was collected from a bed partner or family member. Snoring intensity was evaluated using a 10 cm visual analogue scale (VAS) from 0 to 10: 0 represents no snoring, 1–3 represents minimally annoying, 4–6 represents moderately annoying, 7–9 represents annoying, and 10 represents extremely annoying [18]. We defined 0 as no snoring, 1–3 as mild snoring, 4–6 as moderate snoring, and 7–9 as severe snoring.…”
Section: Methodsmentioning
confidence: 99%
“…The results of that study showed high consistency and concordance, but when the peak level was adjusted to exclude the effect of different volumes of each snoring, the concordance was found to be low. [19] Efforts have also been made to objectively de ne the intensity of snoring. However, owing to the lack of an international consensus on sound intensity for the de nition of snoring, different criteria were applied depending on the investigators.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome measures were assessing snoring frequency per week and snoring loudness using a ten-point visual analog scale (VAS), in which 0 represented no symptoms and 10 represented the most severe symptoms as determined by the patients’ bed partners [ 17 , 43 ]. The snoring frequency was measured by asking the patients’ sleep partners to report the number of days per week on which the patient had symptoms; partners were also asked to assess the average severity of snoring loudness using VAS over the study time.…”
Section: Methodsmentioning
confidence: 99%